Marked intrafamilial aggregation and heritability of aortic flow in a community with prevalent volume-dependent hypertension in Africa. Issue 3 (March 2022) - Yusuf, Suraj M.; Norton, Gavin R.; Peterson, Vernice; Libhaber, Carlos D.; Mmopi, Keneilwe N.; Bello, Hamza; Masiu, Mohlabani; Da Silva Fernandes, Daniel; Tade, Grace; Mthembu, Nonhlanhla; Peters, Ferande; Dessein, Patrick; et al.
Abstract : Aims: Although peak aortic flow ( Q ) is now recognized as a major determinant of hypertension in Africa, current therapy has no proven ability to target this change. The mechanisms of this effect, therefore, require elucidation. We compared the intrafamilial aggregation and heritability of Q to that of the vascular determinants of pulse pressure (PP) and SBP in Africa. Methods: The intrafamilial aggregation and heritability of Q and aortic characteristic impedance ( Z c ) or total arterial compliance (TAC) was determined in 669 participants of 194 families (69 father–mother, 385 parent–child, 157 sibling–sibling pairs) in a community in Africa with prevalent flow-dependent primary hypertension. Haemodynamics were determined from velocity and diameter measurements in the outflow tract (echocardiography) and central arterial pressures. Results: No mother–father correlations were noted for either Q or Z c . However, with adjustments for confounders, parent–child ( P < 0.0001) and sibling–sibling ( P < 0.0001) correlations were noted for Q . Parent–child and/or sibling–sibling correlations were also noted for Z c or TAC but were weaker for Z c and mother–father correlations were noted for TAC. Moreover, Q showed markedly stronger multivariate adjusted heritability estimates ( h 2 = 0.82 ± 0.07, P < 0.0001) than Z c ( h 2 = 0.44 ± 0.10, P < 0.0001)( P < 0.005 for comparisons) and TAC ( h 2 = 0.47 ± 0.08, P < 0.0001)( P < 0.005 for comparisons). Importantly, the heritability of Q was also greater than that for PP ( h 2 = 0.12 ± 0.09, P = 0.11) ( P < 0.0001 for comparisons), or SBP ( h 2 = 0.13 ± 0.10, P = 0.08) ( P < 0.0001 for comparisons). Conclusion: Of the haemodynamic determinants of SBP, peak aortic flow is the most strongly inherited in Africa. Peak aortic flow, therefore, represents an important target for identifying novel therapeutic approaches to controlling SBP in Africa. Abstract : Supplemental Digital Content is available in the text